The SAMI galaxy survey: gas velocity dispersions in low-z star-forming galaxies and the drivers of turbulence. Issue 2 (20th May 2020) - Varidel, Mathew R; Croom, Scott M; Lewis, Geraint F; Fisher, Deanne B; Glazebrook, Karl; Catinella, Barbara; Cortese, Luca; Krumholz, Mark R; Bland-Hawthorn, Joss; Bryant, Julia J; Groves, Brent; Brough, Sarah; et al.
ABSTRACT: We infer the intrinsic ionized gas kinematics for 383 star-forming galaxies across a range of integrated star formation rates (SFR ∈ [10 −3, 10 2 ] M⊙  yr −1 ) at z ≲ 0.1 using a consistent 3D forward-modelling technique. The total sample is a combination of galaxies from the Sydney-AAO Multiobject Integral field Spectrograph (SAMI) Galaxy survey and DYnamics of Newly Assembled Massive Objects survey. For typical low- z galaxies taken from the SAMI Galaxy Survey, we find the vertical velocity dispersion (σ v, z ) to be positively correlated with measures of SFR, stellar mass, H i gas mass, and rotational velocity. The greatest correlation is with SFR surface density (ΣSFR ). Using the total sample, we find σ v, z increases slowly as a function of integrated SFR in the range SFR ∈ [10 −3, 1]  M⊙  yr −1 from 17 ± 3 to 24 ± 5 km s −1 followed by a steeper increase up to σ v, z ∼80 km s −1 for SFR ≳ 1 M⊙  yr −1 . This is consistent with recent theoretical models that suggest a σ v, z floor driven by star formation feedback processes with an upturn in σ v, z at higher SFR driven by gravitational transport of gas through the disc.